γδ T cells recruitment and local proliferation in brain parenchyma benefit anti-neuroinflammation after cerebral microbleeds - Su, Xin; Yang, Shuxian; Li, Yanxiang; Xiang, Zongqin; Tao, Qiao; Liu, Shengde; Yin, Zhinan; Zhong, Liyun; Lv, Xiaoxu; Zhou, Libing (Frontiers in Immunology, 2023)
Background: Cerebral microbleeds (CMBs) are an early sign of many neurological disorders and accompanied by local neuroinflammation and brain damage. As important regulators of immune response and neuroinflammation, the biological behavior and role of γδ T cells after CMBs remain largely unknown. Methods: We made a spot injury of microvessel in the somatosensory cortex to mimic the model of CMBs by two-photon laser and in vivo tracked dynamical behaviors of γδ T cells induced by CMBs using TCR-δGFP transgenic mice. Biological features of γδ T cells in the peri-CMBs parenchyma were decoded by flow cytometry and Raman spectra. In wildtype and γδ T cell-deficient mice, neuroinflammation and neurite degeneration in the peri-CMBs cortex were studied by RNAseq, immunostaining and in vivo imaging respectively. Results: After CMBs, γδ T cells in the dural vessels were tracked to cross the meningeal structure and invade the brain parenchyma in a few days, where the division process of γδ T cells were captured. Parenchymal γδ T cells were highly expressed by CXCR6 and CCR6, similar to meningeal γδ T cells, positive for IFN-γ and Ki67 (more than 98%), and they contained abundant substances for energy metabolism and nucleic acid synthesis. In γδ T cell-deficient mice, cortical samples showed the upregulation of neuroinflammatory signaling pathways, enhanced glial response and M1 microglial polarization, and earlier neuronal degeneration in the peri-CMBs brain parenchyma compared with wildtype mice. Conclusions: CMBs induce the accumulation and local proliferation of γδ T cells in the brain parenchyma, and γδ T cells exert anti-neuroinflammatory and neuroprotective effects at the early stage of CMBs.